2010
DOI: 10.1186/1471-2296-11-97
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of lifestyle beliefs and lifestyle behaviour following stroke: findings from a focus group study of patients and family members

Abstract: BackgroundStroke is a major cause of disability and family disruption and carries a high risk of recurrence. Lifestyle factors that increase the risk of recurrence include smoking, unhealthy diet, excessive alcohol consumption and physical inactivity. Guidelines recommend that secondary prevention interventions, which include the active provision of lifestyle information, should be initiated in hospital, and continued by community-based healthcare professionals (HCPs) following discharge. However, stroke patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 30 publications
2
44
0
4
Order By: Relevance
“…Timing of secondary prevention advice after stroke is important, with difficulties processing information in the acute phase (Allison et al, 2008;Lawrence et al, 2011;Sullivan and Katajamaki, 2009) and poor compliance identified (Skidmore et al, 2008). Participants in this study did not favour brochures/leaflets as an educational means.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Timing of secondary prevention advice after stroke is important, with difficulties processing information in the acute phase (Allison et al, 2008;Lawrence et al, 2011;Sullivan and Katajamaki, 2009) and poor compliance identified (Skidmore et al, 2008). Participants in this study did not favour brochures/leaflets as an educational means.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies indicate that many stroke survivors and carers are ambivalent or dissatisfied with the information received (Wiles et al, 1998;Tooth and Hoffmann, 2004;Lawrence et al, 2011;Mckevitt et al, 2011). Timing of secondary prevention advice after stroke is important, with difficulties processing information in the acute phase (Allison et al, 2008;Lawrence et al, 2011;Sullivan and Katajamaki, 2009) and poor compliance identified (Skidmore et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Almost all studies reported the data collection process. Thirty studies provided the rationale for their research design, 9, 11, 23, 25ā€“27, 29, 31ā€“33, 35, 39, 41, 42, 44ā€“50, 52ā€“54, 58, 62, 65, 66, 70, 71 nine discussed the relationship between researcher and participants, 29, 42, 44, 46, 50, 54, 66, 70, 71 37 reported rigorous data analyses procedures, 4, 7, 9, 11, 24, 26ā€“28, 30ā€“37, 39, 41ā€“46, 48ā€“50, 52ā€“54, 58, 60, 63, 65, 67ā€“70 45 reported the ethical considerations, 4, 7, 9, 23ā€“25, 27ā€“29, 31, 32, 34, 36ā€“50, 52ā€“60, 62ā€“66, 68ā€“71 and 49 reported the recruitment strategy. 7, 9, 11, 23ā€“25, 27ā€“32, 34ā€“63, 65ā€“71 Of the 10 quantitative studies appraised using CEBMa, all clearly addressed the research question, methods, selection of participants, and had a sample representing the population.…”
Section: Resultsmentioning
confidence: 99%
“…Other parts of these resources included beliefs about stroke, healthy lifestyle, caregiver's own capacity and spirituality [12,37,41,45]. The internal resources of the family included the previous quality of the relationship between family caregiver and stroke survivor [48].…”
Section: Family Resources (Bb Factor)mentioning
confidence: 99%